Customer Satisfaction as a Mediator: Service Quality, Repurchase Intention, and Loyalty in Five-Star Hotels At Losari Beach - Dhea Ananda Cantika Rahman; Irene Hanna H. Sihombing; Nyoman Gde Dewa Rucika (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of service quality on repurchase intention and customer loyalty, with customer satisfaction as a mediating variable, in five-star hotels located in the Losari Beach area of Makassar. The sampling method employed was purposive sampling, involving 390 customers as respondents. Data were analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) approach. The results indicate that service quality has a positive and significant effect on repurchase intention, customer loyalty, and customer satisfaction. Customer satisfaction significantly influences both repurchase intention and customer loyalty. In addition to the direct effects, customer satisfaction acts as a partial mediator that strengthens the effect of service quality on repurchase intention and customer loyalty. These findings provide theoretical contributions to the development of marketing management studies, particularly in the five-star hotel sector in Indonesia, by emphasizing the strategic role of customer satisfaction in shaping repeat consumption behavior and loyalty. The practical implications of this research suggest that the management of Hotel Aryaduta Makassar and The Rinra Hotel Makassar should prioritize enhancing the dimensions of assurance, responsiveness, and empathy as key strategies to build customer satisfaction and loyalty.